2013
DOI: 10.1209/0295-5075/102/66008
|View full text |Cite
|
Sign up to set email alerts
|

Does the 8-N bonding rule break down in As 2 Se 3 glass?

Abstract: -The local coordination numbers of As2Se3 glass were determined by a combination of anomalous x-ray scattering experiments, reverse Monte Carlo calculations, and ab initio molecular dynamics simulations. The well-known '8-N bonding rule' proposed by Mott breaks down around the As atoms, exceeding the rule by 7-26%. An experimental prediction based on mean-field theory agrees with the present experimental and theoretical results. The fourfold coordinated As atoms likely form As-As wrong bond chains rather than … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 28 publications
5
24
1
Order By: Relevance
“…The existence of QT units appears, thus, to be strongly tied to temperature and to the way melts are quenched to the glass, consistent with recent Molecular Dynamics studies 55,125 showing that fourfold arsenic does exist in the liquid state, and represent the dominant structural motif at elevated temperatures. Nevertheless, there have been theoretical 30,126 investigations indicating that QT units might be also present in the glass, and the results seem to agree with those obtained experimentally from anomalous X-ray scattering. 31,127 Given these different open issues regarding structure but also dynamics, we report in the present contribution on a systematic investigation with composition of As x Se 1 − x glasses and liquids using First-Principles Molecular Dynamics (FPMD) simulations.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…The existence of QT units appears, thus, to be strongly tied to temperature and to the way melts are quenched to the glass, consistent with recent Molecular Dynamics studies 55,125 showing that fourfold arsenic does exist in the liquid state, and represent the dominant structural motif at elevated temperatures. Nevertheless, there have been theoretical 30,126 investigations indicating that QT units might be also present in the glass, and the results seem to agree with those obtained experimentally from anomalous X-ray scattering. 31,127 Given these different open issues regarding structure but also dynamics, we report in the present contribution on a systematic investigation with composition of As x Se 1 − x glasses and liquids using First-Principles Molecular Dynamics (FPMD) simulations.…”
Section: Introductionsupporting
confidence: 77%
“…Support for the pyramidal local structure in glasses and liquids have been obtained from neutron, [12][13][14][15][16][17][18] X-ray diffraction, [19][20][21][22][23][24] extended absorption x-ray diffraction [25][26][27][28][29] (EXAFS), anomalous X-ray scattering, 30,31 and Nuclear Magnetic Resonance (NMR). [32][33][34][35] In addition, Raman spectroscopy, [36][37][38][39][40][41][42][43][44][45][46] infrared absorbance 9,37,40,[47][48][49] have shown that the spectrum of elemental Se which consists of several modes typical of Se-Se bond vibrations is affected as the As content is changed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Numerous attempts were made to draw a link between the changes in the physical properties of arsenic selenide and the evolution of its molecular structure as the arsenic content varies, both at room temperature, 11,12 and when the temperature is increased, 13 during ageing of the glass, 14 or when irradiated with a laser. 15 To gain some insights into the arsenic selenide glass structures, recent studies relied on molecular dynamics [16][17][18] combined to anomalous X-ray scattering, 19 or 77 Se solid-state Nuclear Magnetic Resonance [20][21][22][23] to characterize the environments and connectivity of selenium and arsenic atoms. Many of these studies hint toward the existence of a small amount of As-As homopolar bond 12,16 with tetravalent arsenic atoms linked to two arsenic and two selenium atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies hint toward the existence of a small amount of As-As homopolar bond 12,16 with tetravalent arsenic atoms linked to two arsenic and two selenium atoms. 19 Moreover, 77 Se NMR spectroscopy can quantify three distinct selenium environments (selenium atoms linked to two, one or zero arsenic atoms) and shows that there is some disorder in the distribution of the lengths of the selenium chains that link arsenic atoms together, as opposed to what is inferred in the chain-crossing model (i.e. when the selenium chains are of similar lengths).…”
Section: Introductionmentioning
confidence: 99%